Correlation between Head Midline Shift CT-Scan with Glasgow Coma Scale in Head Injury Patient at Waled General Hospital, Cirebon, Indonesia - Permana, Aditia; Royyani, Nunik; Ladala, Evan Wahyudy (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Findings on a head CT scan could use the midline shift (MLS) parameter to assess the severity of head injury. Midline shift was also known to serve as an indicator that was frequently associated with the Glasgow Coma Scale (GCS) in head injury patients. A greater degree of midline shift (> 5 mm) indicated a severe head injury that was significantly associated with a lower Glasgow Coma Scale score. The measurement could be performed quickly, although most of the findings that appeared when patients first arrived at the emergency department were generally mild. Aims: This study aims to determine the correlation between midline shift on CT-Scan head and Glasgow coma scale in head injury patients at Waled General Hospital. Methods: This research is analytical observational with a cross-sectional design. The total sampling technique took samples from the medical records of 38 patients out of 81 samples that had been excluded. The study was conducted at Waled General Hospital in June-July 2024 and analyzed using the Spearman correlation test. Results: The results showed that most samples did not show a midline shift with 30 patients (78.9%) and had a GCS score of 13-15 with 22 patients (57.9%). A significant relationship exists between the midline shift on head CT-Scan with the GCS (p = 0.001, r = -0.770) in head injury patients at Waled General Hospital. Conclusion: Most samples did not show a midline shift picture and had a GCS score of 13-15. There was a significant relationship between the midline shift on head CT scans and the GCS in head injury patients at Waled General Hospital. These findings had important implications in clinical practice, particularly in determining triage priorities, predicting the need for surgical intervention, and monitoring patients intensively.